FECUNDITY AND SPAWNING HABITS OF SOME SILVER-BELLIES - Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
The results of fecundity and ova diameter frequency studies on four species of silver-bellies, viz., Secutor insidiator, S. ruconius, Leiognathus dussumieri and Gazza minuta are presented. The former three species seem to have a prolonged spawning seaon, while the last one has a restricted spawning period.